Pengaruh Desain Produk dan Kualitas Produk terhadap Kepuasan Konsumen di Perusahaan Kencana Bordir Tasikmalaya - Tatan Rusmawan; Budhi Wahyu Fitriadi; Barin Barlian (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to determine the influence of product design and product quality simultaneously on consumer satisfaction at the Kencana Bordir Tasikmalaya company. The partial influence of product design and product quality on consumer satisfaction at the Kencana Bordir Tasikmalaya company. The method used in this research is a survey method with a quantitative approach. With a research sample of 96 people as respondents from consumers of the Kencana Bordir Tasikmalaya company. The data used is primary data. The analytical tool used in this research is multiple linear regression using the SPSS version 25 application. The results of simultaneous testing of product design and product quality have a significant effect on consumer satisfaction. Partially, the product design variable has a significant effect on consumer satisfaction, as well as the product quality variable partially has a significant effect on consumer satisfaction.